2020
DOI: 10.1039/d0gc01031f
|View full text |Cite
|
Sign up to set email alerts
|

Production of aromatics from biomass by computer-aided selection of the zeolite catalyst

Abstract: DS-ITQ-2 has been proposed as catalyst for the Diels–Alder (DA) reaction between 2,5-dimethylfuran and ethylene to produce p-xylene based on the fact that the organic molecule employed for its synthesis mimics the DA intermediate cycloadduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Density functional theory calculations demonstrated that the initial DAC step can proceed uncatalyzed, while the dehydration of the oxanorbornene intermediate is effectively catalyzed by Brønsted acids [32–35] . In addition, theoretical calculations point to higher rates when the intermediates of the DAC reaction are confined in zeolite pores [36,37] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory calculations demonstrated that the initial DAC step can proceed uncatalyzed, while the dehydration of the oxanorbornene intermediate is effectively catalyzed by Brønsted acids [32–35] . In addition, theoretical calculations point to higher rates when the intermediates of the DAC reaction are confined in zeolite pores [36,37] …”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] In addition, theoretical calculations point to higher rates when the intermediates of the DAC reaction are confined in zeolite pores. [36,37] Herein, we investigate the potential of amorphous silicaalumina (ASA) catalysts for the production of p-xylene through the DAC reaction of 2,5-DMF with ethylene. ASA are industrially relevant solid acid catalysts due to their large surface area, accessible mesopores, and relatively low cost as compared to zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…[110,111] More recently, a combination of theoretical and experimental results was used to design and synthesize an efficient ab-initio [112] zeolite catalyst for Diels-Alder reaction. [113] According to experimental and computational studies, the limiting step of the overall process is the non-catalyzed Diels-Alder cycloaddition, where the transition state and the final cycloaddition adduct have similar stability. Then, the zeolite design was based on the concept of using organic structure-directing agents that mimic the transition state, proposing a molecule derived from ).…”
Section: Chemsuschemmentioning
confidence: 99%
“…p-xylene ( pXL). 1,15,[20][21][22][23][24] In 2015, around 37 million metric tons of pXL were consumed mostly for the production of poly(ethylene terephthalate) (PET) and polyester fiber. [23][24][25][26] There are reported studies on the synthesis of pXL from biomass-derived DMF, which include a Diels-Alder cycloaddition of ethylene to form the intermediate 1,4 dimethyl-7-oxabicyclo[2.2.1]hept-2-ene, followed by a dehydration step to pXL using different types of zeolites as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…1,15,[20][21][22][23][24] In 2015, around 37 million metric tons of pXL were consumed mostly for the production of poly(ethylene terephthalate) (PET) and polyester fiber. [23][24][25][26] There are reported studies on the synthesis of pXL from biomass-derived DMF, which include a Diels-Alder cycloaddition of ethylene to form the intermediate 1,4 dimethyl-7-oxabicyclo[2.2.1]hept-2-ene, followed by a dehydration step to pXL using different types of zeolites as catalysts. [23][24][25][26][27][28][29] Usually, for this reaction batch systems are used, combined with high reaction temperatures (523 K-623 K), high ethylene pressures (5.0 MPa-7.0 MPa) and long reaction times (24 h-48 h).…”
Section: Introductionmentioning
confidence: 99%